Comparative efficacy of emergency contraception pills - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
As part of the new systematic review, published in Cochrane Database of Systematic Reviews, a comparison was made of the effectiveness of various contraceptive pills.